Dampak Psikologis Akrofobia pada Mahasiswa Fakultas Ilmu Tarbiyah dan Keguruan di Universitas Islam Negeri Sumatera Utara - Ainul Mardiyah; Khairani; Muhammmad Ramadhan (Jurnal Pustaka Cendekia Pendidikan, 2025)
Phobia is a form of anxiety disorder characterized by excessive and irrational fear of certain objects, situations, or activities. One type of phobia that is quite common but often not seriously realized is acrophobia, which is an excessive fear of heights. This disorder not only affects the psychological aspect, but also affects the daily activities of the individual who experiences it. Students as an early adult age group are in a challenging transition period, both academically and socially. When students experience acrophobia, not only is their mental condition disturbed, but also the potential for limitations in participating in certain activities such as field trips, organizations, or outdoor activities that involve heights. In the context of higher education that demands independence and courage, this type of phobia can be an obstacle to students' self-development.